PEMBERIAN PAKAN BERBASIS AKTIVITAS ENZIM PENCERNAAN LARVA IKAN SELAIS (Ompok hypophthalmus Blkr) - Cici Adliana; Usman M Tang; Henni Syawal (Berkala Perikanan Terubuk, 2017)
Are  three  main  enzymes  that  play  in  feed  digestion  that  are  protese, amylase and lipase. The activity of each enzyme develops varies depending on fish species,  feed, and environmental  factors. The aims of this study was to: 1) know the fish morphology development by the mouth opening of selais larvae (O. hypopthalmus Blkr.) 2) determine the relationship of fish larvae age and feed type. 3) determine the relationship of enzyme activity, feed type and larvae survival. 4) determine the feed consumed, digestion rate and growth rate of selais larvae. This study used Complete Randomly Design with 2 factors and 3 replications. The feed type factors are: Artemia salina, Tubifex sp, and shrimp pellet + EZ plus Nutrien Digester and Deliver. Larvae age factors are : 0-7 days, 8-15 days, 16-23 days, and 24-31 days. The result showed that different type of feed and larvae affect the larvae survival. The highest survival rate of 73-98% was found in feed type of Artemia sp. and 0-14 days age, and survival rate of 98-100% was found in feed type of Tubifex sp. and 15-31 larvae age.